The Impact Of Insurtech On The Insurance Business Model In Indonesia - Widyani, Donafeby (Otoritas Jasa Keuangan, 2023)
In Indonesia, the integration of InsurTech into the business process is beginning to manifest, with emerging companies harnessing technology across various aspects, including customer acquisition, underwriting, claims, billing, and customer service. Furthermore, established companies are incorporating technology into specific facets of their business processes to improve overall efficiency and accuracy. Thus, it is intriguing to delve deeper to the phenomenon to understand what factors are driving the growth of InsurTech there, how it spurs business model innovation, what gaps exist between the country’s current insurance business models and the models required for development, and what capabilities existing insurance companies need to fill in these gaps. This is a qualitative study that interviewed 10 participants, which are C-level executives in ten major national and multinational insurance companies in Indonesia. The finding revealed that efficiency gains, achieved through streamlined processes and cost reduction, drive significant investments in InsurTech. Regulatory challenges and technological advancements shape the trajectory of InsurTech. The direct insurer consumer relationship facilitated by InsurTech enhances speed, ease, and transparency in insurance processes. However, challenges such as underdeveloped business models and resistance to innovation exist. Successful InsurTech integration requires a holistic approach, combining creative thinking, supportive leadership, and industry collaboration. InsurTech not only enhances customer experiences but also holds promise for sustainable business growth through operational optimisation in the Indonesian insurance sector.